Pengaruh Citra Merek, Kualitas Produk dan Promosi Terhadap Keputusan Pembelian Pada Solaria - Akbar, Riza Dzikir; Wasino (Jurnal Manajemen Perhotelan dan Pariwisata, 2024)
The purpose of this research is to analyze the impact of brand image, product quality and promotion on purchasing decisions at Solaria. The data collected is primary data obtained through surveys using questionnaires, and then processed using SPSS version 27. The research population is all consumers who visit Solaria. With a sample of 100 respondents selected using technical accidental sampling. The analysis in this research includes multiple linear regression tests. The methods used to analyze data include classical assumption tests such as normality tests, heteroscedasticity tests, multicollinearity tests and linearity tests. Apart from that, the data hypothesis was also tested using the f test and t test. The results of this research conclude that product quality and promotion have a significant influence on purchasing decisions, while the brand image variable does not have a significant influence on purchasing decisions.